Doing history - Donnelly, Mark, 1967- author.
1 online resource.
Keywords: Doing History bridges the gap between the way history is studied in school or as represented in the media and the way it is studied at university level. History as an academic discipline has dramatically changed in recent decades and has been enhanced by ideas from other disciplines, the influence of postmodernism and historians incorporation of their own reflections into their work. Doing History presents the ideas and debates that shape how we do history today, covering arguments about the nature of historical knowledge and the function of historical writing, whether we can ever really know what happened in the past, what sources historians depend on, and the relative value of popular and academic histories. This revised edition includes new chapters on public history and activist histories. It looks at global representations of the past across the centuries, and provides up-to-date suggestions for further reading, presenting the reader with a thorough and current introduction to studying history at an academic level as well as a pathway to progress this study further. Clearly structured and accessibly written, it is an essential volume for all students embarking on the study of history.